2015
DOI: 10.1179/1362171815y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and wear mechanism change by Nb added in slag free self-shielded flux cored wire

Abstract: The iron based hardfacing alloys were produced using slag free self-shielded flux cored wires with varying niobium contents. The results show that NbC acted as the nucleus of primary M 7 (C, B) 3 (M5Cr, Fe mainly) carbides and decreased the amount of M 7 (C,B) 3 carbides when niobium was added into the alloys. When 18 wt-%Fe-Nb (60 wt-%Nb) was added, the microstructure of hardfacing alloy transformed from hypereutectic structure to a eutectic one due to the formation of NbC, which consumed a mass of carbon. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The steps are as follows: extrusion and drawing to prepare a hollow aluminum alloy tube with an outer diameter of 12 mm, filling the prepared seamless aluminum alloy tube with flux powder, sealing the two ends of the tube and then rolling, drawing and winding to obtain a seamless aluminum filler metal wire of Φ 2.4 mm. Alternatively, the online welding method (using special welding machines-such as for high-frequency welding, laser welding or pulsed argon arc welding-to weld the seam) [17,25,26] is a commonly used method for preparing seamless carbon steel and stainless steel flux-cored brazing wires. However, this involves a large welded pipe diameter and poor weldability to thin-walled nonferrous alloy filler metal, and the subsequent processing is difficult, so it has not been popularized and applied in flux-cored filler metal development.…”
Section: Structure and Preparation Of Flux-cored Filler Metalsmentioning
confidence: 99%
“…The steps are as follows: extrusion and drawing to prepare a hollow aluminum alloy tube with an outer diameter of 12 mm, filling the prepared seamless aluminum alloy tube with flux powder, sealing the two ends of the tube and then rolling, drawing and winding to obtain a seamless aluminum filler metal wire of Φ 2.4 mm. Alternatively, the online welding method (using special welding machines-such as for high-frequency welding, laser welding or pulsed argon arc welding-to weld the seam) [17,25,26] is a commonly used method for preparing seamless carbon steel and stainless steel flux-cored brazing wires. However, this involves a large welded pipe diameter and poor weldability to thin-walled nonferrous alloy filler metal, and the subsequent processing is difficult, so it has not been popularized and applied in flux-cored filler metal development.…”
Section: Structure and Preparation Of Flux-cored Filler Metalsmentioning
confidence: 99%
“…Corrosion was found to directly related to porosity [12], so the porosity can be minimised by careful choice of welding consumables [13,14]. Liu et al [15] demonstrated that minimal stomatal sensitivity could be achieved with the new iron-based slag-free self-shielded flux-cored wire due to silicon. The formation of CO gas resulting in the weld pool boiling inhibited the occurrence of porosity.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a series of slag-free self-shielded flux-cored wire with continuity of welding process, high speed of melting, absence of additional gas supply and reduction of slag exhausting [10][11][12]. Since TiB 2 and Nb powders are more expensive than Fe-Nb and Fe-Ti powders, the Fe-Nb and Fe-Ti were added into the wires in this study.…”
Section: Introductionmentioning
confidence: 99%